Dual column chromatography combined with high-resolution mass spectrometry improves coverage of non-targeted analysis of plant root exudates - Alexandra A. Bennett; Teresa Steininger-Mairinger; Çağla Görkem Eroğlu; Aurélie Gfeller; Judith Wirth; Markus Puschenreiter; Stephan Hann (Analytica Chimica Acta, 2024)

No general support for functional diversity enhancing resilience across terrestrial plant communities - Lucrecia Lipoma; Stephan Kambach; Sandra Díaz; Francesco María Sabatini; Gabriella Damasceno; Jens Kattge; Christian Wirth; Scott R. Abella; Carl Beierkuhnlein; Travis R. Belote; Markus Bernhardt‐Römermann; Dylan Craven; et al. (Global Ecology and Biogeography, 2024)
Aim Understanding the mechanisms promoting resilience in plant communities is crucial in times of increasing disturbance and global environmental change. Here, we present the first meta‐analysis evaluating the relationship between functional diversity and resilience of plant communities. Specifically, we tested whether the resilience of plant communities is positively correlated with interspecific trait variation (following the niche complementarity hypothesis) and the dominance of acquisitive and small‐size species (following the mass ratio hypothesis), and for the context‐dependent effects of ecological and methodological differences across studies. Location Global. Time Period 2004–2021. Major Taxa Studied Vascular plants. Methods We compiled a dataset of 69 independent sites from 26 studies that have quantified resilience. For each site, we calculated functional diversity indices based on the floristic composition and functional traits of the plant community (obtained from the TRY database) which we correlated with resilience of biomass and floristic composition. After transforming correlation coefficients to Fisher's Z ‐scores, we conducted a hierarchical meta‐analysis, using a multilevel random‐effects model that accounted for the non‐independence of multiple effect sizes and the effects of ecological and methodological moderators. Results In general, we found no positive functional diversity–resilience relationships of grand mean effect sizes. In contrast to our expectations, we encountered a negative relationship between resilience and trait variety, especially in woody ecosystems, whereas there was a positive relationship between resilience and the dominance of acquisitive species in herbaceous ecosystems. Finally, the functional diversity–resilience relationships were strongly affected by both ecological (biome and disturbance properties) and methodological (temporal scale, study design and resilience metric) characteristics. Main Conclusions We rejected our hypothesis of a general positive functional diversity–resilience relationship. In addition to strong context dependency, we propose that idiosyncratic effects of single resident species present in the communities before the disturbances and biological legacies could play major roles in the resilience of terrestrial plant communities.

Tree demographic strategies largely overlap across succession in Neotropical wet and dry forest communities - Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Dylan Craven; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Bruno Hérault; Catarina C. Jakovac; et al. (Ecology, 2024)
Secondary tropical forests play an increasingly important role in carbon budgets and biodiversity conservation. Understanding successional trajectories is therefore imperative for guiding forest restoration and climate change mitigation efforts. Forest succession is driven by the demographic strategies—combinations of growth, mortality and recruitment rates—of the tree species in the community. However, our understanding of demographic diversity in tropical tree species stems almost exclusively from old‐growth forests. Here, we assembled demographic information from repeated forest inventories along chronosequences in two wet (Costa Rica, Panama) and two dry (Mexico) Neotropical forests to assess whether the ranges of demographic strategies present in a community shift across succession. We calculated demographic rates for >500 tree species while controlling for canopy status to compare demographic diversity (i.e., the ranges of demographic strategies) in early successional (0–30 years), late successional (30–120 years) and old‐growth forests using two‐dimensional hypervolumes of pairs of demographic rates. Ranges of demographic strategies largely overlapped across successional stages, and early successional stages already covered the full spectrum of demographic strategies found in old‐growth forests. An exception was a group of species characterized by exceptionally high mortality rates that was confined to early successional stages in the two wet forests. The range of demographic strategies did not expand with succession. Our results suggest that studies of long‐term forest monitoring plots in old‐growth forests, from which most of our current understanding of demographic strategies of tropical tree species is derived, are surprisingly representative of demographic diversity in general, but do not replace the need for further studies in secondary forests.

Simulated soil erosion predominantly affects fungal abundance in the rapeseed rhizosphere - Julian Ruggaber; Ayten Pehlivan; Rainer Remus; Davide Francioli; Stephan Wirth; Jürgen Augustin; Steffen Kolb (Rhizosphere, 2024)

Root but not shoot litter fostered the formation of mineral-associated organic matter in eroded arable soils - Eva Kaštovská; Michal Choma; Gerrit Angst; Rainer Remus; Jürgen Augustin; Steffen Kolb; Stephan Wirth (Soil and Tillage Research, 2024)

Deadwoods are hotspots for soil functions in old-growth beech forests: monitoring during 15 years after a windthrow event - Yahya Kooch; Azam Nouraei; Stephan Wirth (European Journal of Forest Research, 2023)

Soil functional indicators in different development stages of an oak (Quercus castaneifolia C.A. Mey.) stand - Yahya Kooch; Mohammad Kazem Parsapour; Stephan Wirth (Applied Soil Ecology, 2023)

Comparison of the effects of long-lasting static stretching and hypertrophy training on maximal strength, muscle thickness and flexibility in the plantar flexors - Konstantin Warneke; Klaus Wirth; Michael Keiner; Lars H. Lohmann; Martin Hillebrecht; Anna Brinkmann; Tim Wohlann; Stephan Schiemann (European Journal of Applied Physiology, 2023)
Maximal strength measured via maximal voluntary contraction is known as a key factor in competitive sports performance as well as injury risk reduction and rehabilitation. Maximal strength and hypertrophy are commonly trained by performing resistance training programs. However, literature shows that long-term, long-lasting static stretching interventions can also produce significant improvements in maximal voluntary contraction. The aim of this study is to compare increases in maximal voluntary contraction, muscle thickness and flexibility after 6 weeks of stretch training and conventional hypertrophy training. Sixty-nine (69) active participants ( f = 30, m = 39; age 27.4 ± 4.4 years, height 175.8 ± 2.1 cm, and weight 79.5 ± 5.9 kg) were divided into three groups: IG1 stretched the plantar flexors continuously for one hour per day, IG2 performed hypertrophy training for the plantar flexors (5 × 10–12 reps, three days per week), while CG did not undergo any intervention. Maximal voluntary contraction, muscle thickness, pennation angle and flexibility were the dependent variables. The results of a series of two-way ANOVAs show significant interaction effects ( p < 0.05) for maximal voluntary contraction ( ƞ 2 = 0.143–0.32, p < 0.006), muscle thickness ( ƞ 2 = 0.11–0.14, p < 0.021), pennation angle ( ƞ 2 = 0.002–0.08, p = 0.077–0.625) and flexibility ( ƞ 2 = 0.089–0.21, p < 0.046) for both the stretch and hypertrophy training group without significant differences ( p = 0.37–0.99, d = 0.03–0.4) between both intervention groups. Thus, it can be hypothesized that mechanical tension plays a crucial role in improving maximal voluntary contraction and muscle thickness irrespective whether long-lasting stretching or hypertrophy training is used. Results show that for the calf muscle, the use of long-lasting stretching interventions can be deemed an alternative to conventional resistance training if the aim is to increase maximal voluntary contraction, muscle thickness and flexibility. However, the practical application seems to be strongly limited as a weekly stretching duration of up to 7 h a week is opposed by 3 × 15 min of common resistance training.

How Pt and Pd are hosted in magmatic sulfides, substitutions and/or inclusions? - Hassan M. Helmy; Roman Botcharnikov; Chris Ballhaus; Richard Wirth; Anja Schreiber; Stephan Buhre (Contributions to Mineralogy and Petrology, 2023)

Acute effects of long-lasting stretching and strength training on maximal strength and flexibility in the calf muscle - Konstantin Warneke; Tim Wohlann; Lars H. Lohmann; Klaus Wirth; Stephan Schiemann (German Journal of Exercise and Sport Research, 2023)
The so-called “stretch-induced force deficit” is known from a large amount of research. There are many theories trying to explain the stretch-induced force deficit and increases in the range of motion (ROM) which all offer a stretch training-specific explanation. However, when performing a commonly used strength training session, a reduced maximum strength (MSt) capacity can be assumed as well. Based on this, the aim of the study is to investigate the tension-induced force deficit due to a suprathreshold strength or stretching training stimulus. Therefore, 71 participants (age: 24.1 ± 4.2 years, height: 176.3 ± 5.7 cm, weight: 74.1 ± 7.5 kg) were divided into three groups: static stretching group (SST), strength training group (STR), and control group (CG). To investigate possible mechanical tension-induced force deficits, SST performed a long-lasting static stretching intervention for 1 h using an orthosis, while STR executed a common strength training intervention (5 × 12 repetition) for the plantar flexors. The results show a significant reduction of measured MSt as well as increased ROM for both SST and STR following the interventions. Consequently, we found similar acute effects of stretching and strength training regarding MSt and flexibility. We conclude that the decreased MSt capacities can possibly be attributed to mechanical tension-induced damage of the muscle that is not linked to a specific training method. The improvements in flexibility found in both intervention groups might be attributed to warm up effects when inducing high mechanical tension to large ankle joint angles.

Successional shifts in tree demographic strategies in wet and dry Neotropical forests - Nadja Rüger; Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Dylan Craven; Bruno Hérault; et al. (Global Ecology and Biogeography, 2023)
Aim Tropical forest succession and associated changes in community composition are driven by species demographic rates, but how demographic strategies shift during succession remains unclear. Our goal was to identify generalities in demographic trade‐offs and successional shifts in demographic strategies across Neotropical forests that cover a large rainfall gradient and to test whether the current conceptual model of tropical forest succession applies to wet and dry forests. Location Mexico and Central America. Time period 1985–2018. Major taxa studied Trees. Methods We used repeated forest inventory data from two wet and two dry forests to quantify demographic rates of 781 tree species. For each forest, we explored the main demographic trade‐offs and assigned tree species to five demographic groups by performing a weighted principal components analysis to account for differences in sample size. We aggregated the basal area and abundance across demographic groups to identify successional shifts in demographic strategies over the entire successional gradient from very young ( Results Across all forests, we found two demographic trade‐offs, namely the growth–survival trade‐off and the stature–recruitment trade‐off, enabling the data‐driven assignment of species to five demographic strategies. Fast species dominated early in succession and were then replaced by long‐lived pioneers in three forests. Intermediate and slow species increased in basal area over succession in all forests, but, in contrast to the current conceptual model, long‐lived pioneers continued to dominate until the old‐growth stage in all forests. The basal area of short‐lived breeders was low across all successional stages. Main conclusions The current conceptual model of Neotropical forest succession should be revised to incorporate the dominance of long‐lived pioneers in late‐successional and old‐growth forests. Moreover, the definition of consistent demographic strategies that show clear dominance shifts across succession substantially improves the mechanistic understanding and predictability of Neotropical forest succession.

Influence of maximal strength performance in front squat and deadlift on linear sprint and jump performance in male youth elite basketball players - Konstantin Warneke; Michael Keiner; Stephan Schiemann; Lars Lohmann; Klaus Wirth (German Journal of Exercise and Sport Research, 2023)
Background Strength and speed are two major factors that determine performance in basketball players especially sprinting, jumping and change of direction. This study examined relationships of maximal strength in the front squat and the deadlift with basketball-specific sprint and jump performance tests that are commonly used in test batteries of athletic diagnostics. Materials and methods In all, 42 youth male elite basketball players (age: 14.7 ± 2.4 years, age range: 13–18 years, height: 179.1 ± 15.3 cm, weight: 69.8 ± 19.2 kg) volunteered to take part in the present study. The one repetition maximum (1 RM) in the front squat and deadlift were used to determine maximum strength. Countermovement jump (CMJ) and standing long jump were evaluated to determine jump performance and 5, 10, and 20 m linear sprint as well as agility T‑test were performed to determine sprint performance. Pearson correlation analysis was used to assess the relationships between strength and jump and sprint performance. Results Strong positive correlations were found between maximal strength and jump heights (r = 0.85–0.91, p < 0.001) and strong negative correlations were determined between maximal strength and measured sprint times r = (−0.71 to −0.85, p < 0.001). Conclusion The measured maximal strength in the front squat and deadlift seem to be good predictors for basketball-specific jump and sprint performance. From this, it seems to be beneficial to include training of maximal strength via front squat and deadlift into training routines as well as performance diagnostics.

Evolution of magmatic sulfide liquids: how and when base metal sulfides crystallize? - Hassan M. Helmy; Roman Botcharnikov; Chris Ballhaus; Anastasia Deutsch-Zemlitskaya; Richard Wirth; Anja Schreiber; Stephan Buhre; Tobias Häger (Contributions to Mineralogy and Petrology, 2021)

Biochar mitigates effects of pesticides on soil biological activities - Dilfuza Egamberdieva; Zafarjon Jabbarov; Naveen Kumar Arora; Stephan Wirth; Sonoko Dorothea Bellingrath-Kimura (Environmental Sustainability, 2021)

Biochar mediated control of soil-borne phytopathogens - Burak Alaylar; Medine Güllüce; Dilfuza Egamberdieva; Stephan Wirth; Sonoko Dorothea Bellingrath-Kimura (Environmental Sustainability, 2021)

Novel aspects of age-protection by spermidine supplementation are associated with preserved telomere length - Alexander Wirth; Bettina Wolf; Cheng-Kai Huang; Silke Glage; Sebastian J. Hofer; Marion Bankstahl; Christian Bär; Thomas Thum; Kai G. Kahl; Stephan J. Sigrist; Frank Madeo; Jens P. Bankstahl; et al. (GeroScience, 2021)
Ageing provokes a plethora of molecular, cellular and physiological deteriorations, including heart failure, neurodegeneration, metabolic maladaptation, telomere attrition and hair loss. Interestingly, on the molecular level, the capacity to induce autophagy, a cellular recycling and cleaning process, declines with age across a large spectrum of model organisms and is thought to be responsible for a subset of age-induced changes. Here, we show that a 6-month administration of the natural autophagy inducer spermidine in the drinking water to aged mice is sufficient to significantly attenuate distinct age-associated phenotypes. These include modulation of brain glucose metabolism, suppression of distinct cardiac inflammation parameters, decreased number of pathological sights in kidney and liver and decrease of age-induced hair loss. Interestingly, spermidine-mediated age protection was associated with decreased telomere attrition, arguing in favour of a novel cellular mechanism behind the anti-ageing effects of spermidine administration.

Plant growth response of broad bean (Vicia faba L.) to biochar amendment of loamy sand soil under irrigated and drought conditions - Dilfuza Egamberdieva; Zohreh Zoghi; Khudayberdi Nazarov; Stephan Wirth; Sonoko Dorothea Bellingrath-Kimura (Environmental Sustainability, 2020)
The broad bean ( Vicia faba L.) originated in the Near East, and is cultivated around the world, however, its cultivation is affected by drought stress in several central growing regions of the globe. The present study was designed to determine the effect of biochar on bean plant growth, acquisition of nitrogen (N), phosphorus (P), and potassium (K) and on soil nutrient contents under drought and irrigated conditions. Pyrolysis char from maize (MBC) at 2 and 4% concentrations was used for pot experiments. The shoot and/or root biomass of bean grown in soil amended with 2 and 4% MBC under irrigated condition was increased. Furthermore, increased nodule numbers of bean grown at 4% MBC amendment was observed under both irrigated and drought conditions. P and K uptake of plants under drought conditions increased by 14% and 23% under 2% MBC amendment, and by 23% and 34% under 4% MBC amendment as compared to plants grown without biochar application, respectively. This study demonstrated beneficial effects of biochar produced from maize on growth and nutrient uptake of broad bean, by improving the nodule formation and soil nutritional contents in a sandy loam soil.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Allelopathic effects of the aqueous extract of Rhazya stricta on growth and metabolism of Salsola villosa - Abdulaziz A. Alqarawi; Abeer Hashem; Ashwani Kumar; Al-Bandari Fahad Al-Arjani; Elsayed Fathi Abd_Allah; Basharat A. Dar; Stephan Wirth; Kakhramon Davranov; Dilfuza Egamberdieva (Plant Biosystems, 2018)

Medicinal plants with phytotoxic activity harbour endophytic bacteria with plant growth inhibitory properties - Vyacheslav Shurigin; Kakhramon Davranov; Stephan Wirth; Dilfuza Egamberdieva; Sonoko Dorothea Bellingrath-Kimura (Environmental Sustainability, 2018)

Potential effects of biochar-based microbial inoculants in agriculture - Dilfuza Egamberdieva; Ma Hua; Moritz Reckling; Stephan Wirth; Sonoko Dorothea Bellingrath-Kimura (Environmental Sustainability, 2018)

Continental mapping of forest ecosystem functions reveals a high but unrealised potential for forest multifunctionality - Fons van der Plas; Sophia Ratcliffe; Paloma Ruiz‐Benito; Michael Scherer‐Lorenzen; Kris Verheyen; Christian Wirth; Miguel A. Zavala; Evy Ampoorter; Lander Baeten; Luc Barbaro; Cristina C. Bastias; Jürgen Bauhus; et al. (Ecology Letters, 2018)
Humans require multiple services from ecosystems, but it is largely unknown whether trade‐offs between ecosystem functions prevent the realisation of high ecosystem multifunctionality across spatial scales. Here, we combined a comprehensive dataset (28 ecosystem functions measured on 209 forest plots) with a forest inventory dataset (105,316 plots) to extrapolate and map relationships between various ecosystem multifunctionality measures across Europe. These multifunctionality measures reflected different management objectives, related to timber production, climate regulation and biodiversity conservation/recreation. We found that trade‐offs among them were rare across Europe, at both local and continental scales. This suggests a high potential for ‘win‐win’ forest management strategies, where overall multifunctionality is maximised. However, across sites, multifunctionality was on average 45.8‐49.8% below maximum levels and not necessarily highest in protected areas. Therefore, using one of the most comprehensive assessments so far, our study suggests a high but largely unrealised potential for management to promote multifunctional forests.

Biodiversity and ecosystem functioning relations in European forests depend on environmental context - Sophia Ratcliffe; Christian Wirth; Tommaso Jucker; Fons van der Plas; Michael Scherer‐Lorenzen; Kris Verheyen; Eric Allan; Raquel Benavides; Helge Bruelheide; Bettina Ohse; Alain Paquette; Evy Ampoorter; et al. (Ecology Letters, 2017)
The importance of biodiversity in supporting ecosystem functioning is generally well accepted. However, most evidence comes from small‐scale studies, and scaling‐up patterns of biodiversity–ecosystem functioning (B‐EF) remains challenging, in part because the importance of environmental factors in shaping B‐EF relations is poorly understood. Using a forest research platform in which 26 ecosystem functions were measured along gradients of tree species richness in six regions across Europe, we investigated the extent and the potential drivers of context dependency of B‐EF relations. Despite considerable variation in species richness effects across the continent, we found a tendency for stronger B‐EF relations in drier climates as well as in areas with longer growing seasons and more functionally diverse tree species. The importance of water availability in driving context dependency suggests that as water limitation increases under climate change, biodiversity may become even more important to support high levels of functioning in European forests.

Spatially Heterogeneous Nest-Clearing Behavior Coincides with Rain Event in the Leaf-Cutting Ant Atta cephalotes (L.) (Hymenoptera: Formicidae) - J G Stephan; R Wirth; I R Leal; S T Meyer (Neotropical Entomology, 2015)

Secondary salinity effects on soil microbial biomass - Dilfuza Egamberdieva; Giancarlo Renella; Stephan Wirth; Rafiq Islam (Biology and Fertility of Soils, 2010)